EXPLORING STUDENTS’ PERCEPTIONS OF INTENSIVE LISTENING IMPLEMENTATION IN INDONESIAN HIGHER EDUCATION - Aliya Hana Latifa; Deddy Suryana; Ari Arifin Danuwijaya; Muhammad Handi Gunawan (University of Kuningan, 2025)
Abstract: Intensive listening has gained significant attention in enhancing listening skills among students. While its benefits have been well documented in primary and secondary education, there is a notable gap in research regarding its implementation among university students. This study aims to address the gap by investigating the implementation of intensive listening at a higher education level, particularly exploring the students’ perceptions towards its implementation. By using a qualitative case study design, this study involved first-year students from English language education at one public university in Bandung, Indonesia. Data were collected using open-ended questionnaires, interviews, and classroom observation and analyzed thematically using NVivo software. Findings revealed that the students reported their positive perceptions regarding the implementation of intensive listening in the classroom which enhanced their listening skills, vocabulary, and pronunciation. Nevertheless, they encountered challenges with unfamiliar vocabulary, accent, and rate of speech. Several strategies to cope with the challenges were implemented, and it suggests the critical role of the lecturer in supporting the success of the implementation of intensive listening in the classroom.Keywords: Intensive listening; listening comprehension; listening strategies; university students.